Estimation of Hospital Costs for Colorectal Cancer Care for Nova Scotia - Brian D O'Brien; Murray G Brown; George Kephart (Canadian Journal of Gastroenterology)
BACKGROUND: Colorectal cancer (CRC) is the second most common invasive cancer in Canada. Estimates of the costs of care allow estimation of the cost effectiveness of screening for premalignant and early disease.